Conrad in perspective : essays on art and fidelity - Najder, Zdzisław (New York : Cambridge University Press, 1997)
Zdzislaw Najder, one of the world's leading authorities on Joseph Conrad and author of the major biography Joseph Conrad: A Chronicle (1983), is widely acclaimed for his particular insights into Conrad's Polish background. The fruits of thirty years of Conrad study appear in this landmark volume of his essays, which explore a wide range of topics: Conrad's national and cultural heritage; his fictions, from the unfinished 'Sisters' and Lord Jim to The Secret Agent; his attitude towards Russia in general and Dostoevsky in particular; his concepts of man and society; and the role of the idea of honour in his work. In a series of more general essays Najder goes on to place Conrad's work within a broad European philosophical, political and literary context. Conrad in Perspective offers new insights into the life and work of one of the twentieth century's greatest novelists by one of his most perceptive critics.
1. Introduction, or confession of a mastodon -- 2. Conrad's Polish background, or from biography to a study of culture -- 3. Joseph Conrad's parents -- 4. Joseph Conrad and Tadeusz Bobrowski -- 5. The Sisters: a grandiose failure -- 6. Lord Jim: a Romantic tragedy of honour -- 7. The Mirror of the Sea -- 8. A Personal Record -- 9. Joseph Conrad's The Secret Agent, or the melodrama of reality -- 10. Conrad, Russia and Dostoevsky -- 11. Conrad and Rousseau: concepts of man and society -- 12. Conrad and the idea of honour -- 13. Joseph Conrad: a European writer -- 14. Joseph Conrad after a century -- 15. Joseph Conrad in his historical perspective -- 16. Fidelity and art: Joseph Conrad's cultural heritage and literary programme.
Includes bibliographical references (pages 213-235) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Conrad, Joseph, -- 1857-1924 -- Criticism and interpretation; Conrad, Joseph, -- 1857-1924; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Electronic books; Criticism, interpretation, etc